Carbonatation and Decarbonatation Kinetics in the La2O3-La2O2CO3 System under CO2 Gas Flows - Bahcine Bakiz; Frédéric Guinneton; Madjid Arab; Abdeljalil Benlhachemi; Sylvie Villain; Pierre Satre; Jean-Raymond Gavarri (Advances in Materials Science and Engineering)
The carbonatation of La2O3 oxide and the decarbonatation of lanthanum carbonate phase La2O2CO3 are investigated using thermal and thermogravimetry analyses under CO2 gas flow. The initial phase La2O3 is first elaborated from pyrolysis of a LaOHCO3 precursor. Then, thermal and thermogravimetry analyses are carried out under CO2 flow, as temperature increases then decreases. The carbonatation kinetics of La2O3 is determined at three fixed temperatures. Electrical impedance spectroscopy is performed to determine the electrical responses associated with ionic mobilities and phase changes, in the temperature range 25 to 900∘C. The electrical conduction during heating under CO2 gas flow should be linked to two regimes of ionic conduction of the carbonate ions. From these electrical measurements, the ionic mobility of carbonate ions CO3  2− is found to be close to 0.003 ⋅10−4 cm2 s−1 V−1 at 750∘C for the monoclinic La2O2CO3 phase.